PENERAPAN MODEL PEMBELAJARAN PENEMUAN TERBIMBING DALAM MATERI PECAHAN KELAS VII SMP - Sari, Deni Winda; Rif at, M; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research aimed to know the concept understanding and student learning outcomes by applying a guided discovery learning model in fraction counting operating material in grade VII of junior high school 2 Sanggau Ledo. The method used in this study is a research method with a form of research that is pre-trial with a one-shot case study design. The aspects used in this study consist of understanding students' concepts and learning outcomes. Data calculation techniques use measurement techniques. The tool used consists of student worksheets and student learning outcomes tests. From the results of data analysis, the understanding of concepts in addition material and fractions of assessment is included in the high category and the completeness of student learning outcomes is not met in a classical manner. It was concluded that the guided discovery learning model could not be applied in fraction counting operation material in grade VII of junior high school 2 Sanggau Ledo.Â Keywords: The Application, Guided Discovery Learning Model, Fraction